Kebijakan Indonesia Terhadap Korban Kejahatan Perdagangan Orang di Malaysia (2012-2017) - Dwirivanda, Aditya Rizky; Windiani, Reni (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2020)
Human trafficking as a form of transnational crime has now become a hot issue in international relations and has been widely discussed in any international forums, this is related to the number of victims that increased almost each year. Indonesia is one of the countries affected by this transnational crime activity. In dealing with this crime phenomenon, Indonesian government then took a stand by issuing policies that refer to the Act. Not only domestic policies, Indonesia also has foreign policies by establishing cooperation with Malaysia which is realized in the Joint Police Cooperation Committee as cooperation between the two countries in tackling cross-border crime that occurs at the borders of the two countries. This study aims to look at the policy strategies that Indonesia has in combating crime against trafficking and handling victims, with using the theory of liberalism and international cooperation. This study uses qualitative methods with descriptive analysis and literature review and interview research techniques. This study found many factors that caused victims of human trafficking crimes to be always high in addition to the Government which had policies and cooperation in this matter.